OC-067 Enhanced Perception Of Proximal Gastro-oesophageal Reflux: Impaired Mucosal Integrity Or Distinct Sensory Innervation?. (9th June 2014) - Woodland, P; Lee, C; Aktar, R; Mthunzi, E; Blackshaw, LA; Preston, SL; Sifrim, D
Abstract : Introduction: In patients with GORD, including refractory disease, reflux events reaching the proximal oesophagus are more likely to be perceived than those only reaching the distal oesophagus. There is also experimental data suggesting an increased sensitivity of the proximal oesophagus relative to the distal. As such, the proximal oesophagus is likely to be highly significant in the pathogenesis of GORD symptoms. Reasons for this proximal oesophageal sensitivity are not clear, but may include reflux volume, impairment in mucosal integrity or changes in sensory innervation. It has recently been shown that distal mucosal integrity (its ability to perform a protective barrier function) is more vulnerable to acid exposure in GORD than in controls. The integrity of the proximal oesophagus has not been tested. To our knowledge, there are no studies evaluating mucosal afferent innervation of the distal and proximal oesophagus. We aimed to compare mucosal integrity and afferent nerve distribution in the proximal and distal oesophagus in patients with heartburn without oesophagitis. Methods: In 23 patients with heartburn and 10 healthy volunteers baseline proximal and distal oesophageal impedance was measured in vivo . Oesophageal mucosal biopsies from the distal and proximal oesophagus were taken and baseline transepithelial electrical resistance (TER) was measured in Ussing chambers. Biopsies were examined immunohistochemically for presence and location of calcitonin gene-related peptide (CGRP) immunoreactive nerve fibres. Results: Baseline impedance was higher in the proximal than in the distal oesophagus in healthy volunteers (2935 ± 204 Ω vs. 2234 ± 290 Ω, p < 0.05) and in patients (2949 ± 183Ω vs.1945 ± 235Ω, p < 0.001). However, baseline TER was not significantly different between proximal and distal oesophagus, or between patients with heartburn and healthy volunteers. Mucosal CGRP-immunoreactive nerves were located more superficially in the proximal oesophagus compared to the distal oesophagus in healthy controls (12.3 ± 0.9 vs. 23.8 ± 1.2 cells from lumen, p < 0.001) and in patients (5.7 ± 0.7 vs. 22.2 ± 2.7 cells from lumen, p < 0.0001). Moreover, these nerves were located closer to the lumen in patients with heartburn compared to asymptomatic controls (5.7 ± 0.7 vs. 12.3 ± 0.9, p < 0.001). Conclusion: The baseline mucosal integrity of the proximal oesophagus is not more impaired than that of the distal, nor is it more impaired in patients with heartburn symptoms versus healthy controls. Increased sensitivity of the proximal oesophagus in GORD may instead be associated with a more superficial location of mucosal afferent nerves. Topical protection of the proximal oesophageal mucosa is a potential treatment strategy to reduce this sensitivity. Disclosure of Interest: None Declared.